Formation of scientific outlook and mental education of students - Muhabbat Usmanjonovna, Asrorova; Laylo Najimovna, Orziyeva; Nazira Tashpulatovna, Gaybullayeva; Kunduz Sabirovna, Mustakimova (International Journal of Psychosocial Rehabilitation, 2020)
The formation of the scientific outlook in the younger generation has always been in the spotlight of the leading people of the nation. In all human systems, educated people of the time have made a significant contribution to the world of science in general. Knowledge is the basis of the scientific outlook.